2010
DOI: 10.1080/07391102.2010.10507360
|View full text |Cite
|
Sign up to set email alerts
|

A Conformationally Constrained Peptidomimetic Binds to the Extracellular Region of HER2 Protein

Abstract: Human epidermal growth factor receptor 2 (HER2) is a member of the human epidermal growth factor receptor kinases (other members include EGFR or HER1, HER3, and HER4) that are involved in signaling cascades for cell growth and differentiation. It is well established that HER2-mediated heterodimerization has important implications in cancer. Deregulation of signaling pathways and overexpression of HER2 is known to occur in cancer cells, indicating a role of HER2 in tumorigenesis. Therefore, blocking HER2-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 73 publications
1
31
0
Order By: Relevance
“…The lead compound 5 was shown to be highly selective for HER2-overexpressing cell lines, with an IC 50 value of 0.396 μM in SKBR-3 and 0.896 μM in BT-474 pcell lines and 16.9 μM in MCF-7 cell lines. 28,29 To evaluate the effect of R1 and R3 flanking residues of the central β-amino acid, peptidomimetics with different functional groups at R1 and R3 were evaluated (Table 1). Replacement of the C-terminal amino acid Phe with Tyr (a hydrophibic group with a hydroxyl group) (compound 6 ) or a negatively charged acidic side chain (compound 7 ) resulted in a loss of activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lead compound 5 was shown to be highly selective for HER2-overexpressing cell lines, with an IC 50 value of 0.396 μM in SKBR-3 and 0.896 μM in BT-474 pcell lines and 16.9 μM in MCF-7 cell lines. 28,29 To evaluate the effect of R1 and R3 flanking residues of the central β-amino acid, peptidomimetics with different functional groups at R1 and R3 were evaluated (Table 1). Replacement of the C-terminal amino acid Phe with Tyr (a hydrophibic group with a hydroxyl group) (compound 6 ) or a negatively charged acidic side chain (compound 7 ) resulted in a loss of activity.…”
Section: Resultsmentioning
confidence: 99%
“…28 We have also shown that a peptidomimetic (compound 5 ) exhibits antiproliferative activity in the lower micromolar range and specifically binds to HER2-overexpressing breast cancer cells. 29 To further investigate the structure-activity relationship of compound 5 and its analogs, we investigated the inclusion of different functional groups (amino acids or β-amino acids) in the peptidomimetic and studied their antiproliferative activity in breast cancer cell lines. Conformational constraints were introduced by incorporating a Pro residue in the peptidomimetic sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of homodimers of EGFR suggest that hydrophobic residues such as Leu582, Trp584, and Tyr602 participate in PPI of domain IV to stabilize the interaction of homodimers of EGFR near the transmembrane [26]. The results from our current and previous studies [28, 30] clearly suggest that a peptidomimetic that we designed targets domain IV and inhibits PPI in vitro as seen in the PLA assay. This inhibition in turn has the pharmacological action of inhibition of phosphorylation of the kinase domain and, hence, modulation of the signal for cell growth.…”
Section: Discussionmentioning
confidence: 79%
“…The region of PPI and its inhibition is marked by an oval shape. The model of EGFR:HER2 heterodimer was generated [108,109] using the crystal structures of EGFR (PDB ID 3NJP) [110] and HER2 (PDB ID) [111] with a homodimer of EGFR as a template (PDB ID 3NJP). EGFR: EGF receptor; PPI: Protein–protein interaction.…”
Section: Executive Summarymentioning
confidence: 99%